(untitled) (International Journal of Engineering and Computer Science, 2014)
Keratins are the most abundant protein in epithelial cells of vertebrates and represent the major constituents of skin and its appendages such as nail, hair, feather, and wool. World-wide poultry processing plants produce millions of tons of feather as a waste product annually, which consist of approximately 90% keratin feathers. These feathers constitute a sizable waste disposal problem. Several different approaches have been undertaken for disposing these feather wastes. In the present work soil samples were collected from barber shop and chicken shop waste dump of Allahabad. Among the bacterial isolates three strains (S-1, S-2 and S-3) showed evidence of keratin degradation. Strain S-1 and S-2 were identified as B. subtilis and strain S-3 was identified as B. licheniformis. The keratin degradation was evident by degradation of feathers, sheep wool and hairs used as substrate. Strain S-3 was found to be the best strain for the degradation of keratin waste.